A study on structural variations of the parotid glands - Jayamma, Ch.; Devi, K.V.N. Geetha (International Journal of Research in Medical Sciences, 2017)
Background: The anatomical structural Scenario of the largest Salivary glands, the parotid glands taken for study because of its clinical interventions like parotid abscesses, Sailoliths, growths may effect the intervening neurovascular bundle which passes through the substance of the parotid gland, and also its affiliations towards the scrotum in mumps. The swellings of the parotid glands cause compression on facial nerve. The Injury to the facial nerve during surgical procedures which may produces face muscles paralysis. The parotidectomy for benign and malignant growths warrants the surgeons for facial nerve injury. Methods: The study includes 50 parotid glands in dead fetuses; 20 parotid glands in adult cadavers of formalin fixed specimens. The glands are exposed according to incisions of Cunningham manual. The extents noted, capsule removed. Measurements taken, shapes observed and tabulated. Results: Variations observed and noted for the accessory lobes. The adult parotid glands are Pyramidal shaped (10 out of 10 glands). The foetal glands are 60% are Pyramidal (30 out of 50 glands), 40% are rounded shape (20 out of 50 glands). The apex extension to the carotid triangle is 20% in adult cadavers (2 out of 10 glands); 8% in foctuses (4 out of 50 glands). According to the measurements the length is 2 times more than the width of the gland in pyramidal shaped; the length and width are nearly equal in rounded shaped glands. The accessory parotid glands present in 20% of adult glands, 12% of foetal glands. Conclusions: According to the present Study major number glands are Pyramidal shaped in foctoses than rounded shape. All the adult glands are Pyramidal shaped glands. Accessory lobes present both adult & foetal specimens.